Factors affecting the rate of athlete development from novice to senior elite: How applicable is the 10-year rule? - Oldenziel, K.; Gagne, F.; Gulbin, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
It can be concluded that the '10-year rule' is not applicable to sports development. 69% of novice athletes develop into senior elite representatives in <10 years. Furthermore, it is possible to transfer previous sporting experiences at a late age in order to make a quick transition to elite level. Therefore, future 'rules of thumb' will be contingent upon age, type of sport, and previous experience. This data has implications for talent identification programs, and the intriguing area of sports specialisation. Ongoing analyses aim to determine the factors supporting a fast transition into elite sport.